Binge eating disorder induced by venlafaxine and desvenlafaxine: A case report - Thales Pimenta de Figueiredo; Débora Marques de Miranda; Antônio Marcos Alvim-Soares Júnior; Miss Ana Clara Silva Melo Franco (Brain Disorders)
This case report discusses an unmarried female in her middle-thirties with a history of Recurrent Depressive Disorder. After taking both venlafaxine and desvenlafaxine, she began to show symptoms of Binge Eating Disorder. To alleviate these symptoms, she discontinued the medications and switched to bupropion, which helped her overcome the eating-related issues. However, her depressive symptoms then returned. The report examines how serotonin and norepinephrine reuptake inhibitors work, which may explain the observer phenomenon and clarify the eating behaviors in this case that might initially appear paradoxical. Moreover, it suggests clinicians close monitor outcomes when using such medications, as symptoms worsening might be an adverse effect rather than a disease progression. A diagrammatic timeline of the case report can be observed in Fig. 1.